MANAGEMENT OF TOURIST DESTINATIONS BY THE REGIONAL GOVERNMENT OF GARUT REGENCY - Eden Komarudin Soeardi (Jurnal Ekonomi, 2023)
This study aims to analyze the management of tourist destinations by the Regional Government of Garut Regency. The method used in this research is qualitative research with a case study approach. Data was collected through interviews, observation, and document analysis. The results of the study show that the Regional Government of Garut Regency has implemented several strategies in managing tourist destinations, including improving accessibility and infrastructure, improving service quality, and increasing promotion and branding. However, there are still a number of challenges faced by the Regional Government in managing tourist destinations, such as the lack of community participation and the lack of coordination between related sectors. Therefore, more coordinated and participatory efforts are needed in the management of tourist destinations in Garut Regency.